2006
DOI: 10.1186/1743-1050-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of follicle morphology and oocyte diameter in four mammalian species (mouse, hamster, pig, and human)

Abstract: Background: Laboratory animals are commonly used for evaluating the physiological properties of the mammalian ovarian follicle and the enclosed oocyte. The use of different species to determine the morphological relationship between the follicle and oocyte has led to a recognizable pattern of follicular stages, but differences in follicle size, oocyte diameter and granulosa cell proliferation are not consistent across the different species. In an effort to better understand how these differences are expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
129
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(150 citation statements)
references
References 23 publications
13
129
1
1
Order By: Relevance
“…In addition to developmental distinctions, the mtDNA content of oocytes is also likely to be linked to oocyte dimension. With mammalian oocytes measuring generally between 0.07 and 0.12 mm and New Zealand chinook salmon oocytes between 4.5 and 5.5 mm in diameter, the detected difference in mtDNA content between the two systems appears reasonable (Griffin et al, 2006). However, the key focus of our work was to describe the dilution effect of paternal mtDNA in the fertilized zygote.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to developmental distinctions, the mtDNA content of oocytes is also likely to be linked to oocyte dimension. With mammalian oocytes measuring generally between 0.07 and 0.12 mm and New Zealand chinook salmon oocytes between 4.5 and 5.5 mm in diameter, the detected difference in mtDNA content between the two systems appears reasonable (Griffin et al, 2006). However, the key focus of our work was to describe the dilution effect of paternal mtDNA in the fertilized zygote.…”
Section: Discussionmentioning
confidence: 84%
“…However, several lines of evidence in animal models challenge this belief, suggesting that completion of oogenesis precedes the follicular preovulatory stage. It was shown that, across a spectrum including different species such as hamsters, mice and pigs, full oocyte growth is almost or entirely reached by the time that follicle development has only progressed to the early antral stage [2]. Furthermore, in the cow it is well-established that oocytes are fully competent in completing maturation and supporting development as soon as the follicle reaches the size of 6 mm [19], well before the achievement of the preovulatory stage, corresponding to a diameter of 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the fact that, during the primary, secondary and incipient antral stages of follicle development, the trajectories of oocyte and follicle growth run parallel to each other. Then, as soon as a well-defined antral cavity forms and the somatic compartment generates the two distinct populations of mural and cumulus cells, the size of oocyte stabilizes whilst, until ovulation, the follicle structure experiences a further significant increase in size [2]. Such divergent growth paths, that encompass most of the antrum expansion phase, poses several questions about the significance of the final stages of follicle development and, above all, allude to the possibility that oocytes achieve full developmental competence well before the follicle reaches the final preovulatory stage.…”
Section: Introductionmentioning
confidence: 99%
“…During the early stage of follicle development, the oocyte rapidly increases in size; however, as folliculogenesis proceeds, the growth rate significantly decline and the gamete reaches the maximum size shortly after antral formation (Griffin et al, 2006, Reynaud et al, 2009, Songsasen et al, 2009. During oocyte growth, several organelles including, mitochondria, endoplasmic reticulum and golgi complexes become more abundant (Peter & McNatty, 1980), indicating that energy production and protein synthesis are essential during this process.…”
Section: Mammalian Oocyte Developmentmentioning
confidence: 99%